Effect of Meniscal Ramp Lesion Repair on Knee Kinematics, Bony Contact Forces, and In Situ Forces in the Anterior Cruciate Ligament. Issue 13 (November 2019) - Naendrup, Jan-Hendrik; Pfeiffer, Thomas R.; Chan, Calvin; Nagai, Kanto; Novaretti, João V.; Sheean, Andrew J.; Shafizadeh, Sven T.; Debski, Richard E.; Musahl, Volker
Background: Meniscal ramp lesions are possible concomitant injuries in cases of anterior cruciate ligament (ACL) deficiency. Although recent studies have investigated the influence of ramp lesions on knee kinematics, the effect on the ACL reconstruction graft remains unknown. Purpose/Hypothesis: The purpose was to determine the effects of ramp lesion and ramp lesion repair on knee kinematics, the in situ forces in the ACL, and bony contact forces. It was hypothesized that ramp lesions will significantly increase in situ forces in the native ACL and bony contact forces and that ramp lesion repair will restore these conditions comparably with those forces of the intact knee. Study Design: Controlled laboratory study. Methods: Investigators tested 9 human cadaveric knee specimens using a 6 degrees of freedom robotic testing system. The knee was continuously flexed from full extension to 90° while the following loads were applied: (1) 90-N anterior load, (2) 5 N·m of external-rotation torque, (3) 134-N anterior load + 200-N compression load, (4) 4 N·m of external-rotation torque + 200-N compression load, and (5) 4 N·m of internal-rotation torque + 200-N compression load. Loading conditions were applied to the intact knee, a knee with an arthroscopically induced 25-mm ramp lesion, and a knee with an all-inside repaired ramp lesion. In situ forces in the ACL, bony contact forces in the medial compartment, and bony contact forces in the lateral compartment were quantified. Results: In response to all loading conditions, no differences were found with respect to kinematics, in situ forces in the ACL, and bony contact forces between intact knees and knees with a ramp lesion. However, compared with intact knees, knees with a ramp lesion repair had significantly reduced anterior translation at flexion angles from full extension to 40° in response to a 90-N anterior load ( P < .05). In addition, a significant decrease in the in situ forces in the ACL after ramp repair was detected only for higher flexion angles when 4 N·m of external-rotation torque combined with a 200-N compression load ( P < .05) and 4 N·m of internal-rotation torque combined with a 200-N compression load were applied ( P < .05). Conclusion: In this biomechanical study, ramp lesions did not significantly affect knee biomechanics at the time of surgery. Clinical Relevance: From a biomechanical time-zero perspective, the indications for ramp lesion repair may be limited.